2010
DOI: 10.1111/j.1759-8893.2010.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing indicators of prescribing quality for primary care paediatricians

Abstract: Objective Monitoring and feedback to physicians on their prescribing patterns helps to promote change in the areas where it is needed. However, behaviour and satisfaction of general paediatricians with the routine monitoring of their prescribing has not been measured. We aimed to develop a set of valid indicators of prescribing quality in paediatric primary care practice, and to evaluate the satisfaction of paediatricians with such indicators. Methods Prescribing indicators were chosen by consensus-group techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Nevertheless, the assumption that amoxicillin, and penicillins in general [38], should be the more frequently prescribed antibiotic is supported by the evidence, since this drug is considered the first-choice treatment for the most common infectious diseases in children [2,4,[27][28][29][30]. Large differences were observed in the percentage of amoxicillin or penicillin prescriptions.…”
Section: Qualitative Differences and Rational Drug Usementioning
confidence: 98%
“…Nevertheless, the assumption that amoxicillin, and penicillins in general [38], should be the more frequently prescribed antibiotic is supported by the evidence, since this drug is considered the first-choice treatment for the most common infectious diseases in children [2,4,[27][28][29][30]. Large differences were observed in the percentage of amoxicillin or penicillin prescriptions.…”
Section: Qualitative Differences and Rational Drug Usementioning
confidence: 98%
“…All data about intervention are shown in a previous paper. [23] These educational materials supported the proposed indicators. The programme was applied, quarterly, from January 2006 until October 2007.…”
Section: Designmentioning
confidence: 66%
“…[9] Furthermore, another crucial factor is that PCPs showed their satisfaction with the intervention programme. [23] In an anonymous structured questionnaire, PCPs referred to having changed their own prescribing practice after having received feedback and confirmed that the continuous intervention could help them to improve drug selection. [ Impact of feedback on paediatric practice R. Fernández Urrusuno et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations